Effect of sulfuric acid on the pyrolysis of Douglas fir and hybrid poplar wood: Py-GC/MS and TG studies - Zhou, S.; Wang, Z.; Liaw, S.; Li, Chun-Zhu; Garcia-Perez, M. (Elsevier, 2013)
This paper reports results on the effect of sulfuric acid addition on the pyrolysis of raw and acid washed Douglas fir wood (DFW) (a softwood) and hybrid poplar wood (HPW) (a hardwood). Nitric acid (0.1%) was used to remove the alkali and alkaline earth metals (AAEMs) from the feedstock studied. Sulfuric acid concentrations of 0.05, 0.1, 0.3, and 0.5 wt.% were applied to the ash free and raw feeds priorto pyrolysis tests in Py-GC/MS and TGA. Our results show that the effect of sulfuric acid addition can be explained by the existence of two reaction regimes. In the first reaction regime the content of ash exceeds the amount of sulfuric acid added. Under these conditions, the sulfuric acid is completely neutralized by the AAEMs; as a result, the char yield decreases and the levoglucosan yield increases as the sulfuric acid concentration increases due to the passivation of the catalytic effect of AAEMs. The second reaction regime is where the content of sulfuric acid exceeds the ash content; un-neutralized free sulfuric acid is available to catalyze dehydration, crosslinking, and polycondensation reactions responsible for the formation of extra char. In this regime the charcoal yield increases as sulfuric acid is added. The products detected by Py-GC/MS were classified into four groups: small molecules, small ring molecules, anhydrosugars, and phenolic compounds. The yield of small molecules (ethanedial, methylyinyl acetate, hydroxyacetaldehyde, methyl vinyl ketone, acetic acid, acetol, 2-hydroxyethyl acetateand methyl pyruvate) decreased as the concentration of sulfuric acid increased. The yield of furfural, a product of hemicelluloses dehydration reactions, increased as the content of sulfuric acid increased.The supplementary addition of sulfuric acid to acid washed samples further increased levoglucosan production in more than 50% compared with the control acid washed material. This result suggests that the sulfuric acid could also play a role mitigating undesirable interactions between cellulose and the other constituents in ash-free lignocellulosic materials. Levoglucosenone, a product of levoglucosan dehydration reactions, increased as more sulfuric acid was added. The yield of most methoxylated phenols (2-methoxy-4vinyl-phenol, isoeugenol, eugenol, 2-methoxy-4-propyl-phenol, vanillin,2,6-dimethoxy-4-(2-propenyl)-phenol, 4-hydroxy-2-methoxycinnamaldehyde, syringaldehyde, 3,5-dimethoxy-4-(2-propenyl)-phenol, 1-(4-hydroxy-3,5-dimethoxylphenyl)-ethanone) in acid washed materials decreased as the content of sulfuric acid increased. Overall sulfuric acid has several major effects on the pyrolysis of lignocellulosic materials: passivation of AAEMs, mitigation of undesirable cellulose interactions in lignocellulosic materials, acceleration of dehydration and polycondensation reactions, mitigation of cellulose fragmentation reactions, and reduction of the formation of methoxylatedmono-phenols from lignin.